RESEÑA de: García-Escudero Márquez, Piedad ; Álvarez Rodríguez, Ignacio. "La presentación y proclamación de candidatos electorales". Madrid: CEPC, 2017 - Aranda Álvarez, Elviro (Teoría y Realidad Constitucional, 2018)
-